Robust half-metallic spin-gap in Co2CrAl: doping and strain engineering. (2nd February 2022) - Islam, A; Zulfiqar, M; Nazir, S; Ni, Jun
Abstract: Half-metallic ferromagnetic (HM FM) materials with sizeable HM-gap have grabbed a lot of attention as they provide high spin-filtering and reduce the spin-flipping, which are necessary parameters for the manufacturing of magnetic memory devices. Herein, the effect of 3 d transition metals (TM = Ti, V, Mn, and Fe) doping at Cr site on the electronic and magnetic properties of full-Heusler Co2 CrAl compound is investigated utilizing ab-initio calculations. The negative formation energies for all doped systems confirm their structural stability at ambient pressure. Our results revealed that undoped and all the TM-doped systems exhibit a stable HM FM state. The Cr d yz and d 3 z 2 − r 2 orbitals are mainly responsible for conductivity in the spin-majority channel with a small contribution from d xy / d x 2 − y 2 states in each case. It is also found the admixture of t 2 g and e g characteristics of TM ions in the spin-magnetization density iso-surfaces, where magnetism is discussed by analyzing the electronic spin state configurations. Moreover, it is found that half-metallicity in all systems is robust and can be preserved by the compression/elongation of the unit cell volume up to 10%. Finally, the Bader charge analysis exhibits that all the motifs contain a mixture of covalent and ionic characteristics. Hence, the present work suggests that 3 d TM-doped Co2 CrAl structures are of great interest for the development of extremely capable data storage devices.